AKULTURASI NILAI DAN BUDAYA DALAM SISTEM PENDIDIKAN PESANTREN - Ahmad Hosaini (Universitas Nurul Jadid, 2016)
The aim of this article is to explore the concept of aculturation of value and culture for education on Islamic Boarding School. This article would discuss about the value and culture that are not contradicted to Islamic teaching for eduacation in Islamic Boarding School. And then, how the impact of them can develop the process of teaching and learning in the classroom activities without losing the prinsciples of teaching. In order to know about several beneficial performance of teaching and learning in Islamic Boarding School, this article using the book syarh ta’limul muta’allim as its references. This article will be concluded with an argument that aculturate values and cultures can increase the character of nation-state espicially in education.